Sustained delivery of functional vascular endothelial growth factor from nanoporous silica nanoparticles into a fibrin gel - Karen Besecke; Sarah Zippusch; Florian Helms; Ulrike Böer; Mathias Wilhelmi; Peter Behrens; Nina Ehlert (PLoS ONE, 2025)
The unsolved major issue of large-scale tissue engineering scaffolds is insufficient initial vascularization. The lack of oxygen and nutrient supply for migrating cells inevitably leads to cell death and subsequently to implant failure. One approach to resolve this problem is the development of pre-vascularized tissue constructs. Following this idea, the installation of micro-vessels within a fibrin scaffold is a promising approach. To induce the formation of these micro-vessels a long-term release of vascular endothelial growth factor (VEGF), which is a key player in endothelial growth, is necessary. As drug carriers, nanoporous silica nanoparticles (NPSNPs) were chosen and loaded with VEGF by the interaction with grafted amino groups. Physicochemical characterization (TEM, XRD, N2 physisorption, zeta potential, and thermogravimetric analysis) revealed nanoparticles with approximately 44 nm in diameter, pore sizes of 3 nm, and a successful amino modification of the surface. The recorded release profiles showed a possible long-term release of up to 100 days. With adapted loading concentrations for in vitro testing, the released doses were applied within an in vitro 2D sandwich tube assay with endothelial cells and compared to repeatedly given doses of VEGF in solution. The VEGF released from the NPSNPs led to an equal tube formation, which qualifies them as an effective tool for VEGF delivery inside large-scale tissue constructs that cannot be reached from the outside.